Comparative efficacy and safety of therapeutic strategies for mirror aneurysms: a systematic review and meta-analysis - Javadnia, Parisa; Bahadori, Amir Reza; Naghavi, Erfan; Imeni Kashan, Azadeh; Davari, Afshan; Sheikhvatan, Mehrdad; Tafakhori, Abbas; Shafiee, Sajad; Ranji, Sara (Neurosurgical review, 2024)
Mirror aneurysms are rare and pose therapeutic challenges, with both endovascular and microsurgical options available. Single-stage and two-stage procedures are employed, but the optimal strategy remains unclear. This systematic review and meta-analysis evaluate the efficacy and safety of different therapeutic strategies for managing mirror aneurysms. The study adhered to PRISMA guidelines and comprehensively analyzed data from multiple databases, including Pubmed, Scopus, Embase, Web of Science, and the Cochrane Library, up to 30th September 2024. Statistical analysis utilized the Comprehensive Meta-analysis (CMA) software version 3.0. This systematic review encompasses 42 studies, with 11 studies undergoing meta-analysis. The meta-analysis included 629 participants. Both microsurgical clipping and endovascular interventions achieved high rates of complete occlusion (RROC 1) (ES = 0.896; 95% CI: 0.840 to 0.931; P < 0.001) with low to moderate heterogeneity (I2 = 46.46%). Favorable neurological outcomes (mRS ≤ 2) were significantly achieved among all patients (ES = 0.924; 95% CI: 0.891 to 0.948; P < 0.001) with low heterogeneity (I2 = 15.52%). Subgroup analysis revealed that microsurgical clipping demonstrated superior occlusion rates and more consistent neurological outcomes compared to endovascular treatment. Also, complications were reported in seven studies (n = 492) and included cerebral infarction, hydrocephalus, and vasospasm. As well, mortality and recurrence were rare. Both microsurgical clipping and endovascular interventions are effective and safe for treating mirror aneurysms, with clipping showing superior occlusion rates and consistent outcomes. Single-stage procedures and unilateral craniotomy are associated with better neurological outcomes when feasible.